2019
DOI: 10.1002/ijc.32216
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of circulating cell‐free DNA enables noninvasive tumor detection in myxoid liposarcomas

Abstract: Soft tissue sarcomas (STS) are rare tumors of mesenchymal origin. About 50% of patients with STS experience relapse and more than 30% will die within 10 years after diagnosis. In this study we investigated circulating free DNA (cfDNA) and tumor‐specific genetic alterations therein (circulating tumor DNA, ctDNA) as diagnostic biomarkers. Plasma concentrations and fragmentation of cfDNA was analyzed with quantitative PCR. Patients with STS (n = 64) had significantly higher plasma concentrations and increased fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 31 publications
(68 reference statements)
0
39
0
Order By: Relevance
“…Their results suggest LMS ctDNA levels are associated with disease burden and could further be used as an indicator of disease progression or response to systemic therapy. Others have demonstrated that circulating fusions are detectable in Ewing and myxoid liposarcomas subjects using digital droplet-based PCR [9].…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggest LMS ctDNA levels are associated with disease burden and could further be used as an indicator of disease progression or response to systemic therapy. Others have demonstrated that circulating fusions are detectable in Ewing and myxoid liposarcomas subjects using digital droplet-based PCR [9].…”
Section: Introductionmentioning
confidence: 99%
“…The low predictive value of ctDNA analysis in our study may be a reflection of the small number of patients that showed disease progression in our cohort, and the varied histological subtypes analysed ( Table 1 ). Other more focused studies of individual STS subtypes have used selected/subtype specific mutations to track ctDNA with disease progression in 34–50% of patients analysed [ 15 , 20 ]. In one of these studies focusing on LMS patients, ctDNA was also identified in a much higher proportion of patients with metastatic disease than stable or low disease burden disease (11/16, 69%vs.…”
Section: Discussionmentioning
confidence: 99%
“…The potential usefulness of ctDNA in patient management has been explored in some STS patients with metastatic disease, notably leiomyosarcomas [ 14 , 15 ] among others [ 16 , 17 , 18 , 19 ]. However, to date only one study has investigated ctDNA characteristics in non-metastatic patients with myxoid or well-differentiated/dedifferentiated liposarcomas [ 20 ]. To address this paucity of data, we performed a prospective longitudinal study investigating the cfDNA/ctDNA characteristics of a cohort of non-metastatic STS patients undergoing attempted curative treatment, using three different approaches to quantify ctDNA.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only circulating non-coding RNAs , mainly microRNAs, have been studied in sarcoma liquid biopsy samples 38 , 40 , 54 , 55 . Previous studies have demonstrated that the levels of ctNAs in sarcomas are associated with tumorigenesis, progression and resistance to therapy 40 , 46 , 50 , 54 , 56 - 60 . Therefore, ctNAs show the potential to serve as non-invasive biomarkers in monitoring sarcoma progression and therapeutic response.…”
Section: Detection Methods For Ctnasmentioning
confidence: 99%
“…Subtypes can be distinguished by the presence of the FUS-CHOP fusion oncoprotein (myxoid LPS) and MDM2 overexpression (well-differentiated liposarcoma and dedifferentiated liposarcoma) 146 ; therefore, the above mutations have the potential to be promising biomarkers in LPS. Recently, Braiget al found that the levels of the breakpoint t(12:16) and TERT C228T mutation in plasma in myxoid liposarcomas were associated with tumor burden and tumor dynamics 60 . Although mutant TP53 is not a common somatic event 146 , it has also been identified in plasma from dedifferentiated LPS patients during HDM2 inhibitor therapy 147 .…”
Section: Detection Methods For Ctnasmentioning
confidence: 99%